INDIVIDUAL VARIABILITY OF CARDIAC STRUCTURE AND ITS CLINICAL SIGNIFICANCE (Modern American Journal of Medical and Health Sciences, 2025)
The human heart shows notable individual differences in its anatomical structure, influenced by genetic, environmental, and physiological factors such as age, sex, body size, and physical activity. These variations affect heart size, shape, wall thickness, and chamber dimensions. Distinguishing between normal anatomical variability and pathological changes is crucial for accurate diagnosis and effective treatment of cardiovascular diseases. Advanced imaging techniques like echocardiography and MRI assist clinicians in evaluating these differences. Additionally, genetic research highlights the role of specific gene variants in determining cardiac structure, supporting personalized medicine. Understanding individual cardiac variability enhances patient management and outcomes, emphasizing the need for continued research in this area.